Integrated Management of Sclerotinia Stem Rot of Soybean Including Organically Allowed Fungicides in the Midwest United States - Kelly Debbink; Camila Rocco da Silva; Erin M. Silva; Brian D. Mueller; Darcy E. P. Telenko; Damon L. Smith (PhytoFrontiers)
Sclerotinia stem rot (SSR) is an economically important disease of soybean, especially in the Great Lakes region of the United States. Few studies on SSR have considered organic management practices and how integrated management techniques best apply in these systems. Trials in Wisconsin and Indiana aimed to evaluate management techniques available to organic farmers for their efficacy in SSR control while preserving yield. The practices evaluated included genetically resistant cultivars, tillage techniques, and the application of Organic Materials Review Institute (OMRI)-listed foliar fungicides. The resistant cultivar had significantly lower SSR than the susceptible cultivar in three site-years (P < 0.01). The resistant cultivar also had significantly greater yield than the susceptible cultivar in two site-years (P < 0.05). Using a roller-crimped rye cover crop resulted in mixed results on SSR and yield. No effect on SSR or yield by OMRI-listed foliar fungicides was observed (P > 0.05). Overall, the results emphasize the importance of planting a resistant soybean cultivar to manage SSR in organic farming systems in the Midwestern United States. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.